2017
DOI: 10.1371/journal.pone.0179253
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of minute airflow motions near walls using pappus-type nature-inspired sensors

Abstract: This work describes the development and use of pappus-like structures as sensitive sensors to detect minute air-flow motions. We made such sensors from pappi taken from nature-grown seed, whose filiform hairs’ length-scale is suitable for the study of large-scale turbulent convection flows. The stem with the pappus on top is fixated on an elastic membrane on the wall and tilts under wind-load proportional to the velocity magnitude in direction of the wind, similar as the biological sensory hairs found in spide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The air leakage of the fabricated comb-like cantilever was smaller than that of the normal cantilever when the differential pressure was over 40 Pa, whereas the sensitivity to constant differential pressure was equal to each other. To detect minute airflow motions, the pappus-type sensor was developed to increase the drag force on the cantilever tip [79]. Experimental results indicated that hundreds of hairs of the pappus increased the sensitivity of the sensor by increasing the drag at the tip.…”
Section: Hair-like Airflow Sensorsmentioning
confidence: 99%
“…The air leakage of the fabricated comb-like cantilever was smaller than that of the normal cantilever when the differential pressure was over 40 Pa, whereas the sensitivity to constant differential pressure was equal to each other. To detect minute airflow motions, the pappus-type sensor was developed to increase the drag force on the cantilever tip [79]. Experimental results indicated that hundreds of hairs of the pappus increased the sensitivity of the sensor by increasing the drag at the tip.…”
Section: Hair-like Airflow Sensorsmentioning
confidence: 99%
“…The sensor including its calibration in the BOI is described in detail in [6] . The interested reader is referred to the reference, while we give here only a short review.…”
Section: B the Wall Shear Stress Sensormentioning
confidence: 99%
“…Recently (in 2017), Bruecker and Mikulich developed a novel sensor particularly designed to measure the wall shear stress in low-speed air flows [6]. As reported in [6], its sensitivity and dynamic response were sufficiently good to apply it in the so-called Barrel of Ilmenau (BOI), a large-scale RB experiment, which will be described in detail below. The flow in such a convection cell is known to generate a large-scale circulation (LSC), whose shape mainly depends on the diameter-to-height ratio of the test cell.…”
Section: Introductionmentioning
confidence: 99%
“…The wind field measurement for natural environment is characterized by large wind speed dynamics and fast wind direction changes [ 7 , 8 ]. While in artificial environment, accurate wind speed and direction measurements are needed even the wind speed is small and the wind direction is stable [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%